Double B←N bridged bipyridine-containing polymer acceptors with enhanced electron mobility for all-polymer solar cells. (5th November 2018) - Long, Xiaojing; Yao, Jiuyong; Cheng, Fangfang; Dou, Chuandong; Xia, Yanzhi
Abstract : Two novel polymer electron acceptors based on double B←N bridged bipyridine with enhanced electron mobilities were synthesized for efficient all-polymer solar cells. Abstract : With the aim of developing polymer electron acceptors with high electron mobilities ( μ e ) for all-polymer solar cells (all-PSCs), we synthesized two novel polymer acceptors (P-BNBP-2f andP-BNBP-4f ) containing alternate double B←N bridged bipyridine (BNBP) and 2, 2′-(2, 5-difluoro-1, 4-phenylene)dithiophene/2, 2′-(perfluoro-1, 4-phenylene)dithiophene with extended conjugated structures. In comparison toP-BNBP-4f, P-BNBP-2f exhibits a small π–π stacking distance of 3.60 Å, leading to a sufficient electron mobility of 5.40 × 10 −4 cm 2 V −1 s −1 (measured by the space-charge-limited current method). This μ e value is among the highest values of the conventional polymer acceptors, and is close to the hole mobilities ( μ h ) of high-efficiency polymer donors. Moreover, P-BNBP-2f possesses high-lying LUMO/HOMO energy levels of −3.42/−5.81 eV, which match well with that of the reported excellent polymer donors of 2D-conjugated bithienyl-benzodithiophene- alt -fluorobenzotriazole (J61) and thienyl-substituted BDT with alkoxycarbonyl-substituted thieno[3, 4- b ]thiophene (PBDTTT-E-T). In addition, the blend films based onP-BNBP-2f exhibit intermixed morphologies, which are beneficial for efficient excition dissociation. As a result, all-PSCs withP-BNBP-2f as an electron acceptor work very well and exhibit a power conversion efficiency of 5.46%. These results demonstrate that high electron mobility of a polymer electron acceptor is very important to produce efficient all-PSCs.